1987
DOI: 10.1073/pnas.84.3.643
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroid biosynthesis and embryonic development are disturbed in insects ( Locusta migratoria ) reared on plant diet ( Triticum sativum ) with a selectively modified sterol profile

Abstract: Wheat seedlings germinating in the presence of the systemic fungicide fenpropimorph accumulate 9.8,19-cyclopropylsterols (95% of total sterols) in place of A5-sterols, which are normally produced in these plants. Adult females of the phytophagous insect Locusta migratoria show a dramatic decrease in their cholesterol content when reared on fenpropimorph-treated wheat. These females lay eggs with the ecdysteroid concentration reduced by up to 80% as compared to controls. Injection of fenpropimorph to the insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 9 publications
3
21
0
Order By: Relevance
“…Mortality at pupation, an event that is critically dependent on the moulting hormone, may be due in part to a deficiency in ecdysteroids. Locusts are unable to use 9β-19-cyclopropyl sterols in place of ∆ 5 -phytosterols for ecdysteroid biosynthesis (Costet et al 1987;Corio-Costet et al 1989) and a similar situation may exist for the bertha armyworm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality at pupation, an event that is critically dependent on the moulting hormone, may be due in part to a deficiency in ecdysteroids. Locusts are unable to use 9β-19-cyclopropyl sterols in place of ∆ 5 -phytosterols for ecdysteroid biosynthesis (Costet et al 1987;Corio-Costet et al 1989) and a similar situation may exist for the bertha armyworm.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat seedlings, Triticum aestivum L., treated with fenpropimorph, show a drastically reduced level of their usual ∆ 5 -phytosterols and replacement by 9β, 19-cyclopropyl and ∆ 8 -sterols. Larvae of locusts, Locusta migratoria, fed fenpropimorph-treated wheat displayed delayed development, morphogenic alterations and adults laid eggs in which embryonic development was disturbed (Costet et al 1987;Charlet et al 1988). There have been few other studies on insect utilization of plants with an altered sterol profile, in particular studies on holometabolous insect pests and on insects that harbour symbionts.…”
mentioning
confidence: 99%
“…In conclusion, the changes in sterol content of experimental animals or eggs are stronger in the ester than in the free sterol fraction. Previous analyses performed on the hemolymph of females reared on experimental and normal wheat have shown that the major difference between the two was a 90% reduction of the titer of cholesterol and an accumulation of 5a-cholest-8-en-3P-01 and of 24-methyl pollinastanol (18) in the experimental hemolymph [23]. The present studies show an addition that steryl esters are absent in the blood from control animals and present in trace amounts in experimental animals.…”
Section: Composition Of Free Sterols and Steryl Estersmentioning
confidence: 51%
“…This level was expected to be sufficient because 20E in insects is known to be present at about 10 mg/g DW. [28][29][30] The high level of PEs in these vital plant organs, requiring intensive protection, is well-documented in previous reports. 2,17,20,31) Thus, many of the plants containing PEs appear to be able to accumulate PEs in organs at high levels for protection against non-adapted insects.…”
Section: Discussionmentioning
confidence: 68%